The benefits and challenges of social media in construction industry: a perspective from construction professionals / Siti Nur Aishah Mohd Noor, Nur Syarifah Syahirah Mohd Syed Jaafar and Mohd Khairul Amri Ramly - Mohd Noor, Siti Nur Aishah; Mohd Syed Jaafar, Nur Syarifah Syahirah; Ramly, Mohd Khairul Amri (Universiti Teknologi MARA, Perak, 2021)
In recent years, internet usage and social media have been widely used in Malaysia, the construction industry is one of the industries that are not excluded from this technological trend. This research intended to identify the benefits and challenges of social media in the construction industry among the construction professionals particularly in the northern region area. To identify the usage, the benefit and challenges of social media were also determined in the construction industry whereby it also reflects how far construction professionals rely on social media in their daily works. This research uses quantitative approach in order to collect data via questionnaires distribution from construction professionals. The results revealed that, most of the construction companies agreed that social media provides more advantages and benefits than challenges in the construction industry. This research provides significant data for construction professionals regarding the effectiveness of social media platform particularly in disseminating information for daily communication in construction projects.